The Shelf Life of Wet Noodle Added by Gendarussa (Justicia gendarussa Burm. F.) Leaves Extract - Yuliani Yuliani; Rinten Anjang Sari; Aswita Emmawati; Krishna Purnawan Candra (Talenta Publisher, 2020)
Gendarussa (Justicia gendarussa) is a herbaceous plant with a height of 1-1.5 m. Its stem and leaves extract show antimicrobial and antioxidant activities and have potent cytotoxic activity on the human cancer cell. Gendarussa has a better flavor than stem. Its aqueous extract shows higher extract than ethanol extract. The present study evaluated the preservative effect of aqueous extract of gendarussa leaves (GL) in prolonging the shelf life of wet noodles. The single-factor experiment (GL of 0, 50, 100, 150, and 200 g was extracted in hot water of 100 mL) arranged in a completely randomized design was applied in this research. Total bacterial and mold were observed as well as sensory hedonic characteristics during storage. Data were analyzed using SPSS ver.25. The microbial quality data were analyzed by the Kruskal-Wallis test followed by pair comparison with Bonferroni correction, while the sensory data analyzed by Friedman test continued by Wilcoxon Sign Rank Test. The results showed that the addition of GL aqueous extract (200 g in 100 mL hot water) could prolong the shelf life of wet noodles. The microbial quality of the wet noodle, which preserved at room temperature for 24 h still meet the Indonesian standard of wet noodle (SNI: 2987-2015) for total bacteria and 36 h for total molds. The wet noodles have log cfu/g of 5.35 and 1.58 for total bacterial and mold, respectively. The panelists preferred the color, aroma, texture, and taste of wet noodles produced with the GL aqueous extracts. The most preferred one was wet noodle with the addition of GL aqueous extract at a concentration of 200 g per 100 mL with the characteristic of greenish-white color, not scented with GL, chewy texture, and slightly flavored GL.